PERIODONTAL INDICES IN CHILDREN WITH INSULIN-DEPENDENT DIABETES MELLITUS DURING THE TREATMENT OF GINGIVITIS - Kuz, I.O.; Sheshukova, O.V.; Tkachenko, I.M.; Kazakova, K.S.; Bauman, S.S.; Trufanova, V.P.; Lokhmatova, N.M. (World of Medicine and Biology, 2021)
The oral manifestations of diabetes mellitus are observed in the vast majority of patients, and some dentists indicate 100 % damage to the tissues of the oral cavity. We analyzed the data of hygienic and periodontal indices before and during the treatment in the group of children with chronic catarrhal gingivitis and type 1 diabetes mellitus. We have found a statistically significant difference in a month since the treatment completes, and in 3 month, 6 month, and a year follow-up period. Oral hygiene indices before the treatment demonstrated unsatisfactory level of oral hygiene, but they considerably improved since the treatment had started. Periodontal indices evidenced a moderate degree of the inflammatory process. These values decreased significantly and pointed out mild inflammation in 1 month after the treatment. In 3 months, 6 months and a year follow up period the above indices slightly increased, but, nevertheless, were twice as lower than before the treatment. The use of the proposed treatment scheme had a positive effect on the clinical course of periodontal diseases and contributed to the improvement both in the immediate and long-term follow up.